Plasmacytoid Melanoma of the Urinary Bladder and Lymph Nodes with Immunohistochemical Expression of Plasma Cell Markers Revealing Primary Esophageal Melanoma - Slim Charfi; Sameh Ellouze; Hela Mnif; Ali Amouri; Abdelmajid Khabir; Tahya Sellami-Boudawara (Case Reports in Pathology)
Plasmacytoid variant of melanoma is reported in only rare cases. We present the case of a 54-years-old man admitted for enlarged lymph nodes in the lumbar region. Initial diagnosis of plasmablastic lymphoma/plasma cell myeloma was considered. At our institute, a bladder polyp was removed. Microscopic exam demonstrated dense plasmacytoid cells infiltration with pigment deposits. Immunohistochemical study showed strong expression of HMB45, Melan A, and vimentin. There was focal positivity with S100 protein and CD138/syndecan-1. The diagnosis of metastatic plasmacytoid melanoma was finally established. Clinical exam revealed an esophageal melanoma with melanosis supporting its primary location. Although rarely, melanoma especially plasmacytoid variant may express plasma cell markers which may lead to erroneous diagnosis of plasma cell proliferation. Careful morphological examination for melanin pigment and the use of panel of melanocytic markers are helpful for diagnosis.